The Backpack - Gardner, Tim A. (John Wiley & Sons, Incorporated, 2019)
A guide for being fully equipped to succeed on the journey of life The Backpack: How to Understand and Manage Yourself While Loving Others Along the Way tells the story of Jon, Sofia, and Buddy whose pathways merge on a life-changing flight. Written by a senior consultant with the Flippen Group (a world-wide leader in self-awareness training), the book brings together an angry passenger, a wise flight attendant, and a down-home cowboy. Their chance meeting leads to the ride of their lives as they fully grasp the importance and meaning of their backpacks. As this engaging story reveals, self-awareness is like a backpack! If we are to be prepared to succeed on the journey of life, we need to know and accept which backpack is ours, decide what we need to put in it or take out of it, and be fully aware of how our backpacks are affecting all of the other passengers around us. The question is: Are we whacking the other passengers with our backpack as we travel through life. . . or are we helping them? Offers life lessons on self-awareness written in the form of a funny and engaging story Shows how we can lighten, fill and understand our "backpack" in order to lead a more successful life Written by a senior consultant with the Flippen Group The Backpack offers a story that explores the concepts of self-awareness and other-awareness, including the importance of appreciating your personality, living by your core values, mentally preparing for your day, being aware of your impact on others and packing your backpack wisely.